İçimizdeki Devlet: Türkiye’de Devletin Sıradanlaşması ve Öznenin Devletleşmesi. - Cömert, Metehan; Sümbül, Uğur (PRAKSIS, 2026)
Looking at the state not only "from above" but also "from below" and making the responses found in ordinary citizens’ cognitive schemas an object of inquiry—what does this tell us about the state? This study goes beyond established approaches that rigidly define the state as a purely external, material, and bureaucratic apparatus, and instead, it strives to understand how the state itself becomes intrinsic to the subject’s emotional world, desires, and modes of action. Following the theoretical thread of Pierre Bourdieu’s On the State, the article focuses on the state’s capacity to naturalize itself by penetrating individuals’ cognitive structures rather than its physical and symbolic manifestations of violence. Inspired by Sabahattin Ali’s The Devil Inside Us and adapting that metaphor to explore "the state within us", the study presents a distinctive portrayal of a "subject becoming state" in the Turkish context and attempts to shed light on the processes that transform the subject from a passive recipient exposed to the state into an active agent who appropriates authority as an object of desire. The fundamental claim here is that the subject produces a regime of "surplus" that thinks, feels, and acts like the state even when not demanded and sometimes even in a way to cover the state’s shortcomings. By examining the psychic presence of the state and its manifestations in habitus, the text argues that the state has become a doxa in Turkey, deeply engraved in emotional and mental schemas. It concludes with a tribute to the agency of the ordinary person who continues to exist despite the looming shadow of the state.